2007
DOI: 10.2308/jis.2007.21.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Signal Words and Signal Icons in Application Control and Information Technology Exception Messages—Hazard Matching and Habituation Effects

Abstract: Information technology (IT) users encounter signal words (e.g., “Warning”) and signal icons (e.g., an exclamation point) in “exception messages.” The first of two experiments reported in this paper examines the “arousal strength” associated with signal words and icons that commonly appear in exception messages. An elicitation exercise was completed by 316 participants, in which each viewed exception messages containing combinations of signal words and icons and provided their perception as to the severity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 21 publications
3
58
0
Order By: Relevance
“…A technical error also caused some participants to be shown incorrect images in the Purpose and Control tasks, resulting in 568 participants in these conditions. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A technical error also caused some participants to be shown incorrect images in the Purpose and Control tasks, resulting in 568 participants in these conditions. 2 …”
Section: Discussionmentioning
confidence: 99%
“…While runtime requests provide context to the user, a decade of usability research has shown that users may become habituated to these warnings, making them ineffective [2,6,8,23,25]. Because habituation increases with each warning exposure [15], researchers have studied ways to minimize unnecessary warnings [24] and to make important warnings more salient [5].…”
Section: Background and Related Workmentioning
confidence: 99%
“…They could choose the most preferred number where 1 indicate strongly disagree and 7 indicates strongly agree. Studies by [15,17] also conducted the similar survey method to access the end users insights of the current implementation of security warnings however different in scenario used. The Likert-scale is chosen because it is easy to construct, have a high probability of producing a dependable scale and it is easy to be comprehend by the participants [18].…”
Section: Methodsmentioning
confidence: 99%
“…Studies by [15] revealed how the users of IT perceive the severity of hazard and detailed assessment of the signal icons and signal words. They claimed that by combining signal words and signal icon in a security warnings, the level of hazard perceive by the end users are higher as shown in Table I.…”
Section: ) Failures Communication Deliverymentioning
confidence: 99%
“…However, overly frequent active warnings (e.g. from false positives) lead to habituation effects [1]. Thus, there are many situations in which passive indicators seem to be more promising and should therefore be further investigated.…”
Section: Security Interventions In the Web Contextmentioning
confidence: 99%